2019
DOI: 10.5539/jas.v11n11p162
|View full text |Cite
|
Sign up to set email alerts
|

Shading on Yield and Quality of Lettuce Cultivars in Semiarid Conditions

Abstract: Lettuce is a crop originating from temperate climate, and for this reason, when cultivated in semiarid region, characterized by high luminosity and temperature, major losses in productivity and quality occur. The objective of this work was to evaluate the influence of different levels of shade on yield and quality of lettuce cultivars in semiarid conditions. The experiment was conducted under field conditions at the Human and Agricultural Sciences Center at State University of Paraiba, Brazil, in randomized bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Additionally, to reduce the negative effects of high radiation and temperatures on crop production, shading is frequently used to limit and avoid intense solar radiation entering the greenhouse. This process is accelerated by high indoor air temperature caused by the accumulation of heat waves [44,45]. Ahemd et al [41] and Laur et al [42] also demonstrated that combining shading with evaporative cooling via a fogging system can lower indoor air temperature and impact the appropriate microclimate for lettuce growth.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, to reduce the negative effects of high radiation and temperatures on crop production, shading is frequently used to limit and avoid intense solar radiation entering the greenhouse. This process is accelerated by high indoor air temperature caused by the accumulation of heat waves [44,45]. Ahemd et al [41] and Laur et al [42] also demonstrated that combining shading with evaporative cooling via a fogging system can lower indoor air temperature and impact the appropriate microclimate for lettuce growth.…”
Section: Discussionmentioning
confidence: 99%